2006
DOI: 10.1002/jcp.20773
|View full text |Cite
|
Sign up to set email alerts
|

Diphosphorylation of the myosin regulatory light chain enhances the tension acting on stress fibers in fibroblasts

Abstract: Regulation of the contractile force is crucial for cell migration, cell proliferation, and maintenance of cell morphology. Phosphorylation of the myosin II regulatory light chain (MRLC) is involved in these processes. To show whether the diphosphorylation of MRLC increases the tension acting on stress fibers, changes in the stiffness of fibroblasts expressing wild-type MRLC and a mutant type, which cannot be diphosphorylated, on treatment with lysophosphatidic acid (LPA) were examined by a mechanical-scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 29 publications
2
57
0
Order By: Relevance
“…Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and western blotting were performed as previously described [8]. Information on the primary antibodies used in this study is presented in Supplemental Table 2.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and western blotting were performed as previously described [8]. Information on the primary antibodies used in this study is presented in Supplemental Table 2.…”
Section: Western Blottingmentioning
confidence: 99%
“…Since phosphorylation of MRLC enhances cellular contractile force [8], reduction of MBS85 expression may increase cellular contractile force by increasing MRLC phosphorylation. Cellular contractile force is the sole contributor to the mechanical function of organs and tissues such as the heart and skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…To survey molecular mechanisms as to how cyclic stretch affect the cellular elasticity response by a single step-like stretch, we focused on phosphorylation of MRLC, which are thought to contribute to cellular elasticity [15]. First, we examined changes in pp-MRLC with a single step-like stretch and/or with cyclic stretches.…”
Section: Resultsmentioning
confidence: 99%
“…First, we examined changes in pp-MRLC with a single step-like stretch and/or with cyclic stretches. Previous reports have shown that pp-MRLC increases intracellular contractile force and cellular elasticity [15], and diphosphorylation can be induced by a single step-like stretch [16]. To quantify changes in pp-MRLC, we stained cells with anti-pp-MRLC and measured the intensity ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that so-called "tensional homeostasis" exists at the single cell level (Mizutani et al, 2004). Moreover, this mechanical response originates in the diphosphorylation of myosin regulatory light chain of myosin II combined with F-actin, which increases cellular tension acting on stress fibers (Mizutani et al, 2006). SPM is unique positioned to visualize not only the surface topography but also the spatial distribution of the local viscoelasticity of living cells in a culture medium (Radmacher et al, 1996;Haga et al, 2000).…”
Section: Uniaxial Deformation Devicementioning
confidence: 93%